Is routine growth monitoring effective? A systematic review of trials. Issue 3 (1st March 2000) - Garner, Paul; Panpanich, Ratana; Logan, Stuart
Abstract : BACKGROUND: Growth monitoring consists of routine measurements to detect abnormal growth, combined with some action when this is detected. It aims to improve nutrition, reduce the risk of death or inadequate nutrition, help educate carers, and lead to early referral for conditions manifest by growth disorders. As primary care workers world wide invest time in this activity, evidence for its benefits and harms was sort. INCLUSION CRITERIA: Studies: randomised or quasi-randomised controlled trials of growth monitoring. Interventions: regular growth monitoring, combined with some intervention targeted at abnormal growth, compared with controls. Outcomes: anthropometric measures; referrals to primary and specialist care, or community services; maternal knowledge, anxiety, and satisfaction; child morbidity and mortality. COMPARISONS: Routine growth monitoring compared with no routine growth monitoring; routine growth monitoring by plotting onto a standard chart compared with monitoring with no chart. SEARCH STRATEGY: Cochrane controlled trials register; World Health Organisation and World Bank publications; contact with specialist community paediatricians working in the field. RESULTS: Two trials met the inclusion criteria. One compared growth monitoring with no growth monitoring, in a cluster randomised trial nested in a nutritional intervention programme, and detected no difference in nutritional outcomes between the two groups. Another trial compared growth monitoring with and without a standard chart, measuring maternal knowledge of women about nutrition. It showed small numerical differences in test scores. DISCUSSION AND IMPLICATIONS: Current policies appear to be based on the opinion that investment in the activity has worthwhile health benefits, and does no harm. No reliable evidence was found to support or refute this.